Modified Primers for the Identification of Nonpathogenic Fusarium oxysporum Isolates That Have Biological Control Potential against Fusarium Wilt of Cucumber in Taiwan - Wang, Chaojen (Public Library of Science, 2013)
Previous investigations demonstrated that Fusarium oxysporum (Fo), which is not pathogenic to cucumbers, could serve as a biological control agent for managing Fusarium wilt of cucumber caused by Fo f. sp. cucumerinum (Foc) in Taiwan. However, thus far it has not been possible to separate the populations of pathogenic Fo from the nonpathogenic isolates that have biological control potential through their morphological characteristics. Although these two populations can be distinguished from one another using a bioassay, the work is laborious and time-consuming. In this study, a fragment of the intergenic spacer (IGS) region of ribosomal DNA from an Fo biological control agent, Fo366, was PCR-amplified with published general primers, FIGS11/FIGS12 and sequenced. A new primer, NPIGS-R, which was designed based on the IGS sequence, was paired with the FIGS11 primer. These primers were then evaluated for their specificity to amplify DNA from nonpathogenic Fo isolates that have biological control potential. The results showed that the modified primer pair, FIGS11/NPIGS-R, amplified a 500-bp DNA fragment from five of seven nonpathogenic Fo isolates. These five Fo isolates delayed symptom development of cucumber Fusarium wilt in greenhouse bioassay tests. Seventy-seven Fo isolates were obtained from the soil and plant tissues and then subjected to amplification using the modified primer pair; six samples showed positive amplification. These six isolates did not cause symptoms on cucumber seedlings when grown in peat moss infested with the isolates and delayed disease development when the same plants were subsequently inoculated with a virulent isolate of Foc. Therefore, the modified primer pair may prove useful for the identification of Fo isolates that are nonpathogenic to cucumber which can potentially act as biocontrol agents for Fusarium wilt of cucumber.